The effect of high protein products consumption on albumin serum in stunted children: A systematic review and meta-analysis - Resti, Nina; Syauqy, Ahmad; Anjani, Gemala; Jaswir, Irwandi; Afifah, Diana Nur (Progress in Nutrition, 2025)
Background and aim: To evaluate the effect of high-protein products on serum albumin levels for preventing stunting in children by combining statistical results from multiple studies meeting the inclusion criteria, providing a more precise estimate of the intervention's impact.Methods: A comprehensive electronic search was conducted in Web of Science, Scopus, PubMed, and Semantic Scholar databases, covering publications from 2015 to 2024.Methods: The study was designed with a PRISMA diagram for systematic reviews and Meta-analyses with standard guidelines and software Review Manager 5.4. The PICOTS framework (participants, intervention, comparison, outcomes, timing, and study design) guided the selection process. Inclusion criteria focused on trial studies investigating the effects of high-protein product consumption on serum albumin levels in stunted children.Results: Meta-analysis using RevMan 5.4 demonstrated significant heterogeneity among studies was 0.85 (95% CI: -0.03-1.72); Chi² = 59.29, (I² = 92%,p